Framing News of Hamas Attacks: Automated Journalism Practices at NewsGPT.ai - Suprayitno, Dede; Wardani, Ayu; Yuliandri, Putrawan (Jurnal Kajian Jurnalisme, 2024)
The Hamas militant group's attack on the population of Israel was recorded in the Model Automated Journalism platform, NewsGPT.ai. The platform, led by CEO Alan Levy, claims to be the world's first AI-generated news. This research aimed to reveal the news framework presented by the NewsGPT.ai platform regarding the Hamas attack on Israel on October 7, 2023. Specifically, it investigated the way NewsGPT.ai positions Palestine and Israel in the news coverage. It used a qualitative approach with Robert N. Entman's framing theory. Entman's main concepts include defining problems, diagnosing causes, making moral judgments, and treatment recommendations. Within 10 selected news, an information bias regarding the Hamas attack on Israel on October 7, 2023, was found. The news produced by NewsGPT.ai is subjective, in terms of the theme, reporting angle, and diction for the news object. Hamas tends to be associated with terrorists. The word terrorist is dominant in the text, referring to the actions of Hamas. Some terms that typically appear are acts of terrorism, terrorist attacks, fighting terrorism, and terrorist organizations. NewsGPT.ai presents information bias regarding this issue with a dominant emphasis on strengthening support for Israel. The use of AI in journalism, especially NewsGPT.ai, still shows bias towards certain groups.